History and Educational Argument. History, Education and History of Education in the Crisis of the First Modernity - Magalhães, Justino (2017)
In the background of Rationalism and in the course of Modernity, history, as a discourse, rationality, memory and «master of life», and education, as a rational order of present and regarding to construct the future, met each other. History constitutes the foundation, condition and meaning behind education. Education was at the basis of Modernity. History is a retrospective vision of the process and the degree of development that humanity has achieved. Education encompasses conduction and transformation. The crisis and break away from the scholastic, in the transition from the first Modernity, are correlatives of the affirmation of history as a subject, with a discourse, a method and a curricular status. One century later, at the end of XIX century, history and education met each other as history of education and educational argument for a re-elaboration of memoryexperience, with a projective sense. Thinking out education with history has conferred the historian and historiographical (in)formation an irreplaceable position and a contribution in the equation of the present. I propose to document these ideas, with a European view and including a reference to the Portuguese case.